Perbedaan Syariah sebagai Wahyu dan Syariah sebagai Hasil Pemikiran pada Masyarakat Era Modernisasi - Agustar, Armi (Jurnal Syariah dan Hukum Komparatif, 2022)
This research departs from the doubts of modern society, regarding sharia as revelation and sharia as a result of thought. The progress of modern society has resulted in major changes to the mindset and lifestyle, especially the understanding of sharia as revelation and sharia as a result of thought. This type of research is qualitative descriptive, with an interdisciplinary approach and utilizes comparative, vertical, horizontal and diagonal comparative analysis methods. The purpose of this study is to explain that the difference between sharia as revelation and sharia as a result of thought and the relationship between the two. The conclusion of the notion of sharia and revelation itself and the relationship between sharia texts and others. The definition of revelation in its form is the Qur'an and Hadith, while sharia is the result of people's thoughts or understanding of the revelations that are said (mujtahid). The results of the mujtahid's thoughts on the Qur'an and Hadith are the products of thoughts such as: Tafsir, ijtihad, fiqh, judges, fatwas, jurisprudence, and codification.